Prognostic Value of Dehydroepiandrosterone Sulfate for Patients With Cardiovascular Disease: A Systematic Review and Meta‐Analysis. Issue 5 (May 2017) - Wu, Ting‐Ting; Chen, Yuan; Zhou, Yun; Adi, Dilare; Zheng, Ying‐Ying; Liu, Fen; Ma, Yi‐Tong; Xie, Xiang
Abstract : Background: The aim of the present study was to estimate the impact of dehydroepiandrosterone sulfate (DHEAS) on the prognosis of patients with cardiovascular disease by performing a systematic review and meta‐analysis. Methods and Results: The Embase, PubMed, Web of Science, CNKI, and WanFang databases were searched up to September 5, 2016, to identify eligible studies. The quality of each study was assessed using the Newcastle‐Ottawa Scale. The association between DHEAS, either on admission or at discharge, and cardiovascular disease outcomes were reviewed. The overall risk ratio for the effect of DHEAS on all‐cause mortality and fatal and nonfatal cardiovascular events was pooled using a fixed‐effects or a random‐effects model. The publication bias was evaluated using funnel plots. Twenty‐five studies were included for systematic review. The follow‐up duration ranged from 1 to 19 years. Eighteen studies were included in the meta‐analysis. We found that lower DHEAS levels indicated a significant increased risk for all‐cause mortality (risk ratio, 1.47; 95% CI, 1.38–1.56 [ P <0.00001]), fatal cardiovascular event (risk ratio, 1.58; 95% CI, 1.30–1.91 [ P <0.00001]), and nonfatal cardiovascular event (risk ratio, 1.42; 95% CI, 1.24–1.62 [ P <0.0001]) in patients with cardiovascular disease. Conclusions: Patients with cardiovascular disease who have lower DHEAS levels may have poorer prognosis than those with higher DHEAS levels.